Morphological Analysis of Derivational English Suffixes With Reference To Enola Holmes Movie - Ni Putu Sri Wandhana Dewi; I Wayan Arka; Novita Mulyana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
One approach to creating words is through derivation. The Plag theory, which claims that there are four types of suffixes—nominal, adjective, verb, and adverb—is used to determine this suffix's form. Comparably, while examining functions, class-maintaining suffixes and class-changing suffixes are two different types of components. The purpose of this study is to recognize the varieties and evaluate the roles of English derivational suffixes in the Enola Holmes movie. The qualitative methodology was used in this study. The information used for this study was taken completely from the Enola Holmes movie by Nancy Springer. In order to define the rules and limitations for creating new words in English, the researcher uses the theory from Plag in a book titled Word-Formation in English to describe the formulation of the problems in this study. The study's findings revealed that there were nominal suffixes, verb suffix, and adjectival suffixes in the data. Noun forming nouns were the only type of class-maintaining suffixes that were present. The verb forming noun, adjective forming noun, noun forming verb, noun forming adjective, and adjective forming adverb were the six components that made up class-changing suffixes.